Moonlighting proteins: beacon of hope in era of drug resistance in bacteria. (2nd January 2023) - Yadav, Pramod; Singh, Raja; Sur, Souvik; Bansal, Sandhya; Chaudhry, Uma; Tandon, Vibha
Abstract: Moonlighting proteins (MLPs) are ubiquitous and provide a unique advantage to bacteria performing multiple functions using the same genomic content. Targeting MLPs can be considered as a futuristic approach in fighting drug resistance problem. This review follows the MLP trail from its inception to the present-day state, describing a few bacterial MLPs, viz., glyceraldehyde 3′-phosphate dehydrogenase, phosphoglucose isomerase glutamate racemase (GR), and DNA gyrase. Here, we carve out that targeting MLPs are the beacon of hope in an era of increasing drug resistance in bacteria. Evolutionary stability, structure–functional relationships, protein diversity, possible drug targets, and identification of new drugs against bacterial MLP are given due consideration. Before the final curtain calls, we provide a comprehensive list of small molecules that inhibit the biochemical activity of MLPs, which can aid the development of novel molecules to target MLPs for therapeutic applications.